Can we prevent type I diabetes? - Mathieu, Chantal (Henry Stewart Talks, 2007)
Type 1 diabetes is an autoimmune disease characterized by an immune destruction of the insulin producing beta-cells in the islets of Langerhans of the pancreas, As these cells are the only cells in the body that are able to synthesize and secrete insulin in a regulated manner, destruction of these cells renders the patient dependent on exogenous insulin administration for survival, Interventions aimed at preventing the disease have not been successful until now, but lessons from the animal models open new perspectives
Archived at 2021/02/25